The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000023696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of auricular point pressing therapy on postoperative pain of fracture

Abstract: Background: In clinical practices, postoperative fracture patients are often treated with analgesics. As one of the alternative therapies for nondrug analgesia, auricular point pressing has advantages of simple operation, easy to use, no injury and adverse reactions, and great potential for development. In this study, the effect of auricular point pressing therapy on postoperative pain of fracture was objectively evaluated through the method of meta-analysis, so as to provide evidence for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…After removing duplications, the titles and abstracts of 267 trails were further evaluated. Next, the full texts of the remaining 21 records were assessed, and 14 trails were fnalized for inclusion in our meta-analysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. 2022.…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplications, the titles and abstracts of 267 trails were further evaluated. Next, the full texts of the remaining 21 records were assessed, and 14 trails were fnalized for inclusion in our meta-analysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. 2022.…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of green complementary and alternative therapy, auricular acupuncture therapy has a good analgesic effect during the perioperative period and has been widely used in gynecology, orthopedics, anorectal, and other fields (10). According to the theory of bioholography, the close association between auricular acupoints and zangfu-meridians is the basis for the clinical treatment of pain (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that acupuncture is primarily used to treat pain, and acupuncture has significant effects on pain relief, with high safety and few side effects (8,9). A previous meta-analysis demonstrated that auricular point pressing, a traditional acupuncture therapy, combined with conventional analgesia can effectively relieve postoperative pain and reduce the consumption of different types of analgesic drugs (10). According to the theory of bioholography, the auricle forms a holographic reflex path from the homologically connected neurons in the brain and acts through the holographic connection of neurons in the brain (11).…”
Section: Introductionmentioning
confidence: 99%
“…Multimode analgesia is a kind of analgesic program that combines the application of drugs with different methods or mechanisms to make them have synergistic effects, so as to reduce the dosage of analgesics and improve the analgesic effect, and has achieved remarkable effects in clinical application [ 2 ]. In recent years, in addition to drug analgesia, it has been reported that auricular point pressing bean as a nondrug intervention can reduce the dosage of early postoperative analgesics by stimulating the auricle acupoints, without vomiting, nausea, and other adverse reactions [ 3 ]. Therefore, this study combined multimode analgesia and auricular acupoint therapy for perioperative patients with meniscus injury surgery, comprehensively analyzed the physical and mental stress, rehabilitation quality, and pain degree, in order to provide new ideas for improving the rehabilitation quality of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Multimode analgesia is a kind of analgesic program that combines the application of drugs with di erent methods or mechanisms to make them have synergistic e ects, so as to reduce the dosage of analgesics and improve the analgesic e ect, and has achieved remarkable e ects in clinical application [2]. In recent years, in addition to drug analgesia, it has been reported that auricular point pressing bean as a nondrug intervention can reduce the dosage of early postoperative analgesics by stimulating the auricle acupoints, without vomiting, nausea, and other adverse reactions [3].…”
Section: Introductionmentioning
confidence: 99%